Chrysalis-Like Graphene Oxide Decorated Vanadium-Based Nanoparticles: An Extremely High-Power Cathode for Magnesium Secondary Batteries. Issue 7 (30th March 2020) - Pagot, Gioele; Vezzù, Keti; Nale, Angeloclaudio; Fauri, Maurizio; Migliori, Andrea; Morandi, Vittorio; Negro, Enrico; Di Noto, Vito
Abstract : Rechargeable batteries based on magnesium virtually provide high volumetric capacity, safety, and cost savings thanks to the abundance, dendrite-free electrodeposition, and environmentally green properties of Mg metal anode. The lack of cathodes that can deliver high currents at high potential is one of the principal bottlenecks that limit the entrance of Mg batteries into the market. Here we report the synthesis and characterization of a novel cathode for magnesium secondary batteries based on graphene oxide (GO) and vanadium (V) active species. Thermogravimetric analysis, structural and vibrational analyses, and high-resolution electron microscopies elucidate the complex architecture that characterizes the proposed material and that bestows exceptional electrochemical properties to the cathode. The proposed synthesis is able to give rise to V-based nanoparticles with a very porous surface and wrapped inside a chrysalis-like GO ordered superstructure. Finally, a coin cell device is assembled using a Mg metal anode and the proposed material as cathode. This prototype is able to deliver good capacities when cycled at high current rates (1000 mA g −1 ) in a higher potential range with respect to classical cathodes for Mg batteries. Thus, a sufficient power (1.70 W g −1 ) is obtained, making this battery promising towards the substitution of lithium batteries.